Development of an extended reactor configuration to analyze preferential segregation impact on spray autoignition. (15th October 2021) - Bouali, Z.; Reveillon, J.; Pera, C.
Highlights: Methodology to create a heterogenous two-phase reactor. Investigate the effect of preferential spray segregation. Effect of spray properties on the cool flame process. Impact of the initial temperature on the most reactive mixture fraction. Effect of the preferential segregation on the autoignition delay. Abstract: The chemical reactor concept, usually based on a homogeneous mixture, is extended to non-homogeneous two-phase flows to study the impact of preferential segregation on the autoignition of an n-heptane spray in air. To introduce inhomogeneities, two-dimensional reactors are resolved thanks to direct numerical simulations (DNS) with Eulerian/Lagrangian description to follow the evolution of the carrier phase and the dispersed evaporating droplets, respectively. Two-way coupling is considered through exchange of mass, momentum, and energy between the carrier-gas phase and the dispersed phase. A chemistry mechanism with 29 species and 52 reactions was chosen to describe the chemical reaction paths. Several simulations were performed with various initial gas temperatures (i.e. low, intermediate and high) and various geometrical and physical characteristics of the preferential segregation. Results confirmed that evaporative cooling, vapor mass quantity and turbulence mixing play important roles in the two-phase flow autoignition. We discussed the ignition delay as well as the location of the first hot spots according to the initial gas temperatures. The dependence of most reactive mixture fraction on initial carrier-gas temperature is non-monotonic, thus there is a strong correlation between the first autoignition location and low scalar dissipation rate. On the other hand, the autoignition can start whatever the vorticity magnitude is.